Plyometric training practices of Brazilian Olympic sprint and jump coaches: toward a deeper understanding of their choices and insights - Loturco, I.; Pereira, L. A.; Freitas, T. T.; Moura, T. B. M. A.; Mercer, V. P.; Fernandes, V.; Bishop, C.; Moura, N. A.; Zajac, A. (Journal of Human Kinetics, 2023)
Plyometric training is extensively used by coaches to enhance neuromuscular performance in a wide variety of sports. Due to the high demands of sprint speed and power output in elite sprinters and jumpers, sprint and jump coaches are likely to have great knowledge on this topic. Undoubtedly, this expertise is even more pronounced for Olympic coaches, who work with some of the fastest and most powerful athletes in the world, and who are required to continually maintain these athletes at optimal performance levels. Describing and discussing the practices commonly adopted by these coaches in detail and extrapolating this experience to other sport coaching contexts and disciplines may be extremely relevant. The current article presents, explores, and illustrates the plyometric training practices of Brazilian Olympic sprint and jump coaches, with a special focus on training programming and exercise selection.